Theolinguistic analysis of al-Farabi’s treatise "Usul ‘Ilm At-Tabi’a" (based on the chapter "’aql") - Mukhitdinov‬‏, R.S. (Journal of Oriental Studies, 2021)
The works of Abu Nasr al-Farabi continue to attract the attention of scholars, who quite actively and fruitfully studying the philosophical treatises of the Second Aristotle, contributed to their translation into a number of languages ​​in the world. This article attempts to make a theological and linguistic analysis of the first Chapter "’Aql" (intelligence, mind) of al-Farabi’s treatise "Kitab makalat ar-rafia fi usul at-tabia". The aim of the study is to reveal both linguistic and theological meaning through the analysis of words, terms and concepts used by the Second Teacher after Aristotle. Since the object of the research is the text of the Chapter "’Aql" in the treatise of the medieval scholar-encyclopedist, the key methods were the methods used in the study of text, incl. hermeneutic method for the study of verses from the Quran and hadiths of the Prophet Muhammad. In the process of considering the treatise, we will study the religious point of view of al-Farabi, where discussion issues among scholars will be taken into account, as well as a philosophical, namely metaphysical point of view based on the text from the Quran and hadiths functioning in the treatise. The study is interdisciplinary, as it connects linguistics and religion, and in particular Islamic theology. The results of the study will contribute to the disclosure of linguistic meanings of theological concepts, as well as the implementation of linguistic analysis of religious texts.